Sistema informático de planeación y control, en la producción de banano de la Empresa Novellmax S.A del cantón Babahoyo - Herrera Macías, Rubén Alfredo (2012)
The present investigation work Is With Respect to the creation of a COMPUTER SYSTEM AND CONTROL OF gliding, IN THE PRODUCTION OF BANANA TREE IN THE COMPANY OF THE CANTON NOVELLMAX SA Babahoyo Whose action field for the commercial production area to study what Was Made on the main That Problematic fields it confronts the company in the process of STI information of banana tree production. That I have Developed topics on computer systems and Explain Software Developments, reference it made taming WAS and the Necessity of building a system Determined Processes That type of information statistics everything in the process of banana tree production, like the physical to Improve Control of states in Its cellar of storage of field materials and packer, for this way to save time and work to Obtain information to correct and Organized . The creation of This system has as objective photo to generate production reports Where the administrative part and Its efficient producer Have me picture the information registered in the same one. You use the XP Methodology That is a process of iterations of software development, this Methodology Has Been Because the central pillar to Develop Each One of the stages for the software Which is conformed, an analysis of the context taming Developed That One Carries out when to Beginning the process of this investigation allowed the field to know the Processes and flows of the current information of the company and identifies the process flows you That Were Considered for the computer system. AlsoCarriesouttheonefieldinvestigation,byMeansof thesurveyandtheinterview,thedeficienciesWhichDemonstratedThatthecompanyNovellmaxSAHADFacilitatingActivitiestocarryoutthethesystem.